Strategi Komunikasi Pemasaran Dalam Meningkatkan Jumlah Siswa Di SMK Mambaul Hisan Kabupaten Blitar - Darul Sundariani (Program Pascasarjana Universitas Gajayana, 2019)
Marketing communication is an activity to establish communication that aims to help marketing activities. The marketing communication that is used as a strategy in increasing the number of students means that communication is woven to market educational institutions so that they can increase the number of students in these educational institutions every year. Marketing communication is also used in educational institutions. Namely with educational institutions offering the best educational services and facilities they have to meet the needs and desires of prospective students. This indicates that the seriousness of the management of private education institutions to attract sympathy for prospective students because students are one source of funding for private education institutions. But in reality today there are also many educational institutions that do not operate anymore or no longer offer educational services, one of which is due to a lack of interest in prospective students who enroll in the relevant educational institutions. One of the reasons is poor marketing communication so that the interest of prospective students becomes less. So with good marketing communication it will always increase the number of students in educational institutions every year.